Arteriovenous Loops Enable Free Tissue Transfer With Otherwise Inadequate Local Donor and Recipient Vessels - TREMP, MATHIAS (In Vivo, 2020)
Background/Aim: Free flap reconstruction with damaged or diseased vessels is a challenging problem. We describe our case series using an arteriovenous loop or bypass surgery with free flaps for complex defect reconstructions at the lower extremity and the pelvic region. Patients and Methods: In this single-center retrospective cohort study 11 consecutive patients (mean age=73 years, range=53-88 years) were operated on, between June 2016 and August 2018. Patients were reconstructed with free gracilis flaps (n=8), free latissimus dorsi flap (n=1) and chimeric scapular flap (n=1), respectively. Results: The mean loop length was 30 cm (range=12-40 cm). The loop/bypass revision rate was 27% (3/11), and the overall flap loss rate was 20% (2/10). After a mean follow-up time of 17 months (range=12-24 months), the limb salvage rate was 75% (6/8). Conclusion: We successfully reconstructed complex defects with poor recipient vessels using arteriovenous loops or bypass surgery and free flaps.